2018
DOI: 10.12688/f1000research.15505.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding and managing cholesterol gallstones

Abstract: The high prevalence of cholesterol gallstones, the availability of new information about pathogenesis, and the relevant health costs due to the management of cholelithiasis in both children and adults contribute to a growing interest in this disease. From an epidemiologic point of view, the risk of gallstones has been associated with higher risk of incident ischemic heart disease, total mortality, and disease-specific mortality (including cancer) independently from the presence of traditional risk factors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 217 publications
(209 reference statements)
0
62
0
14
Order By: Relevance
“…There is currently an increasing number of studies about the role of the gut microbiome as a key link in the pathogenesis of GSD [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The main factors contributing to the formation of gallstones are defective gallbladder motility, metabolism and secretion of cholesterol and bile acids [ 12 ]; the gut microbiota is actively involved in the regulation of bile acid metabolism, changing the size and composition of the bile acid pool [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently an increasing number of studies about the role of the gut microbiome as a key link in the pathogenesis of GSD [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The main factors contributing to the formation of gallstones are defective gallbladder motility, metabolism and secretion of cholesterol and bile acids [ 12 ]; the gut microbiota is actively involved in the regulation of bile acid metabolism, changing the size and composition of the bile acid pool [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an altered postprandial gastric emptying occurs either with or without “in situ” gallbladder , suggesting that this defect is independent of the physical presence of gallstones, and possibly linked with mechanisms, which also influence gastrointestinal motility at different levels of the gastrointestinal tract . The extent and timing of gastric emptying worsen after gallbladder removal, pointing to the presence of altered pathways involving bile flow and/or signalling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that UDCA had no effect on gallstones and some had an effect. There is no consensus on the medical or surgical treatment of pediatric gallstones (21,22). Cholecystectomy was an adopted treatment in all pediatric patients with symptomatic gallstone and gallstone complications (5,11).…”
Section: Discussionmentioning
confidence: 99%